2014
DOI: 10.1177/1550059414532443
|View full text |Cite
|
Sign up to set email alerts
|

The Antidepressant Treatment Response Index as a Predictor of Reboxetine Treatment Outcome in Major Depressive Disorder

Abstract: Biomarkers to predict clinical outcomes early during the treatment of major depressive disorder (MDD) could reduce suffering and improve outcomes. A quantitative electroencephalogram (qEEG) biomarker, the Antidepressant Treatment Response (ATR) index, has been associated with outcomes of treatment with selective serotonin reuptake inhibitor antidepressants in patients with MDD. Here, we report the results of a post hoc analysis initiated to evaluate whether the ATR index may also be associated with reboxetine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Cordance and cingulate theta power are closest to proof of concept, with studies reporting successful treatment prediction across different medication classes and study designs (14,29,31,4749,51,105). ATR has been successful across medication classes, but only when tested by its original developers (58,59). A direct and identical replication of at least some of those findings is still necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Cordance and cingulate theta power are closest to proof of concept, with studies reporting successful treatment prediction across different medication classes and study designs (14,29,31,4749,51,105). ATR has been successful across medication classes, but only when tested by its original developers (58,59). A direct and identical replication of at least some of those findings is still necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Norepinephrine (NE) is a neurotransmitter essential for stress reactivity, resilience, and arousal, and NE signaling is thought to be dysregulated in several psychiatric disorders [1][2][3]. Medications targeting the noradrenergic system are used to treat anxiety and depression [4], and recent studies have suggested that guanfacine, an α2A adrenergic receptor agonist (α2AR), could be effective for treating pediatric anxiety disorders [5], as well as stress-induced relapse in cocaine-users [6][7][8][9] and in smokers [10]. Animal models have also identified effects of guanfacine on behaviors related to stress response, anxiety, and depression [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A qEEG biomarker, the Antidepressant Treatment Response (ATR) index, has been associated with outcomes of treatment with SSRIs in patients with MDD. In an open study of norepinephrine reuptake inhibitor reboxetine, the ATR index predicted response with 70.6 % sensitivity and 87.5 % specifi city, and remission with 87.5 % sensitivity and 64.7 % specifi city (Caudill et al 2014 ). These results suggest that the ATR index may be a useful biomarker of clinical response during NRI treatment of adults with MDD.…”
Section: Eeg To Predict Adverse Effects and Evaluate Antidepressant Ementioning
confidence: 98%